FINANCIAL SECURITY AS THE MAIN FACTOR ENSURING THE STABILITY AND COMPETITIVENESS OF A JOINT-STOCK COMPANY - Urazbaeva Ilmira Konysbaevna (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study investigates the role of financial security as a critical determinant of the stability and competitiveness of joint-stock companies, with a specific focus on Uzbekistan’s corporate experience. Method: Using a qualitative-descriptive approach, the research integrates a literature review with an analysis of real-world data, including capital structures, financial performance indicators, and regulatory developments affecting Uzbek joint-stock companies. Results: The findings show that firms with strong financial security—marked by capital adequacy, liquidity, solvency, and risk management—are more resilient to economic shocks and better able to pursue competitive growth strategies. Conversely, the decline in the number of joint-stock companies in the late 2000s reflects the consequences of stringent capital requirements and high leverage, while ongoing reforms in corporate governance and equity financing indicate progress toward improved financial stability and competitiveness. Novelty: The study contributes by contextualizing the concept of financial security within a transitional economy, demonstrating how financial resilience not only secures survival but also enhances market competitiveness, thereby offering theoretical insights and practical implications for corporate financial management in emerging markets.